Control induced instabilities in fluidized bed spray granulation. (September 2020) - Palis, Stefan
Abstract: This contribution is concerned with the stability problems occurring during the operation of continuous fluidized bed spray granulation processes with external sieve mill cycle. These processes are in general operated by a mass controller, which guarantees that the overall mass of particles in the granulation chamber stays in well-defined bounds. It is well-known that, depending on the milling diameter, instabilities may occur, which result in a nonlinear limit cycle of the particle size distribution. To overcome this problem two approaches have been proposed in the literature, constrain the admissible parameter space to exclude regions of instability and design additional stabilizing control loops. In the present contribution, the cause of this instability phenomenon will be studied. It will be shown that the instability is not inherent to the process, which turns out to be open-loop stable over the studied parameter range, but due to the mass controller. More specifically, it will be demonstrated that the zero dynamics of the granulation process become unstable for certain parameter ranges resulting in closed-loop unstable process behavior. To point out, that this behavior does not depend on the specific mass controller design procedure, three prototypical mass controllers of practical relevance are designed and analyzed. Highlights: Stability analysis of continuous fluidized bed spray granulation with and without mass controller. Investigation of the possible destabilizing effect of widely applied mass controllers. Analysis of the parameter-dependent zero dynamics of continuous fluidized bed spray granulation processes.